Review of Neuroleon Navás of West Africa with descriptions of four new species (Neuroptera, Myrmeleontidae) - Michel, Bruno; Akoudjin, Massouroudini (Zootaxa, 2012)
The Neuroleon species of sub-Saharan West Africa are reviewed. Eight species are recorded: N. drosimus Navás, N. lapidarius nov. sp., N. modestus (Navás), N. nubilatus (Navás), N. rapax nov. sp., N. raptor nov. sp., N. pardalice (Banks), and N. ruber nov. sp. A ninth species, N. nigericus Navás, of which no specimens could be examined, is tentatively maintained in the genus Neuroleon pending examination of the type. Three new synonymies are established. Seven species are removed from the genus Neuroleon. N. pardalice is recorded from the region for the first time. The species are illustrated and keyed.